FLORENCE: a randomized, double-blind, phase III pivotal study of febuxostat versus allopurinol for the prevention of tumor lysis syndrome (TLS) in patients with hematologic malignancies at intermediate to high TLS risk - Spina, M; Nagy, Z; Ribera, J M; Federico, M; Aurer, I; Jordan, K; Borsaru, G; Pristupa, A S; Bosi, A; Grosicki, S; Glushko, N L; Ristic, D; et al. (Annals of oncology, 2015)
BACKGROUND: Serum uric acid (sUA) control is of key relevance in tumor lysis syndrome (TLS) prevention as it correlates with both TLS and renal event risk. We sought to determine whether febuxostat fixed dose achieves a better sUA control than allopurinol while preserving renal function in TLS prevention. PATIENTS AND METHODS: Patients with hematologic malignancies at intermediate to high TLS risk grade were randomized to receive febuxostat or allopurinol, starting 2 days before induction chemotherapy, for 7-9 days. Study treatment was blinded, whereas daily dose (low/standard/high containing allopurinol 200/300/600 mg, respectively, or fixed febuxostat 120 mg) depended on the investigator's choice. The co-primary end points, sUA area under curve (AUC sUA1-8) and serum creatinine change, were assessed from baseline to day 8 and analyzed through analysis of covariance with two-sided overall significance level of 5%. Secondary end points included treatment responder rate, laboratory and clinical TLS incidence and safety. RESULTS: A total of 346 patients (82.1% intermediate TLS risk; 82.7% assigned to standard dose) were randomized. Mean AUC sUA1-8 was 514.0 ± 225.71 versus 708.0 ± 234.42 mgxh/dl (P < 0.0001) in favor of febuxostat. Mean serum creatinine change was -0.83 ± 26.98% and -4.92 ± 16.70% for febuxostat and allopurinol, respectively (P = 0.0903). No differences among secondary efficacy end points were detected. Drug-related adverse events occurred in 6.4% of patients in both arms. CONCLUSION: In the largest adult trial carried out in TLS prevention, febuxostat achieved a significant superior sUA control with one fixed dose in comparison to allopurinol with comparable renal function preservation and safety profile. CLINICAL TRIAL REGISTRATION: NCT01724528.
Keywords: senioři nad 80 let; alopurinol; Humans; Uric Acid; prognóza; kyselina močová; lidé; Aged, 80 and over; hematologic malignancy; antiuratika; mladý dospělý; Febuxostat; Female; Double-Blind Method; syndrom nádorového rozpadu; lidé středního věku; Allopurinol; Prognosis; tumor lysis; rizikové faktory; Male; staging nádorů; následné studie; Follow-Up Studies; Tumor Lysis Syndrome; Risk Factors; Adult; dvojitá slepá metoda; dospělí; kidney injury; senioři; febuxostat; Hematologic Neoplasms; hematologické nádory; Aged; Neoplasm Staging; Middle Aged; ženské pohlaví; mužské pohlaví; Gout Suppressants; Young Adult; allopurinol